Gender Roles, Work, and Women’s Mobility in Indonesia: Labour Migration Contexts - Zakiah Hasan Gaffar (FISIP Universitas Tanjungpura, 2019)
Previous studies suggest that women’s migration may pose particular difficulties, both for the individuals involved and for their families and communities because it conflicts with the usual expectation that women will fulfil their ascribed gender roles as daughters, mothers, and wives. To understand this conflict, it necessarily involves the examination of the prevalent cultural and social values in the local context of West Kalimantan,and in Indonesia, in particular how gender and power relations influence the bargaining position of women as workers and members of society. My emphasis is on the cultural norms and practices regarding gender roles and gender responsibilities in Malay societies in West Kalimantan, particularly, and in Indonesia, generally. This paper provides a context for discussion of women’s migration experiences and mobility, by firstly identifying the relevant literature which discusses issues of gender roles, work, and gender and mobility. The link between gender, mobility, and labour migration is then explored.